The Influence of Reading Ability on the Translation Learning Outcomes of Students at Gontor for Girl First Campus - Rahman, Nurul Insani; Mahmudi, Ihwan; Aulia, Siti Sarah; Khumairah, Siti Salwa; Saidah, Lailatus (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Translation is one of the most essential skills in learning any language, including Arabic, as it facilitates understanding texts from other languages and enhances overall language acquisition. At Gontor for Girls First Campus, particularly among fifth-grade female students of Islamic Teacher Training Collage, translation plays a significant role in academic success. However, many students still encounter challenges in translating Arabic texts effectively. One of the primary factors believed to influence translation performance is reading comprehension. Students with strong reading comprehension skills are better able to grasp the meaning of Arabic texts, thereby improving the accuracy and fluency of their translations.This study aims to investigate the influence of reading comprehension on the translation performance of fifth-grade female students at Islamic Teacher Training Collageduring the 2023–2024 academic year. Employing a quantitative approach with a survey method, the study involved a sample of 110 students. Data were collected through reading and translation tests, along with documentation. The Spearman rho correlation test, conducted using SPSS software, revealed a significant correlation between reading comprehension and translation performance, with a Sig. (2-tailed) value of 0.000 < 0.05. Reading comprehension accounted for 12.6% of the variance in translation outcomes, while the remaining 87.4% was attributed to other factors. These findings suggest that although reading comprehension has a measurable impact on translation ability, it is not the sole determinant. Therefore, future research should explore additional cognitive, pedagogical, and affective variables that may contribute to students success in translation. This study contributes to the growing body of literature on language acquisition by underscoring the critical role of reading comprehension in translation learning.